(untitled) (Research, Society and Development, 2020)
To identify the exonic regions in the DNA sequence of Chromosome 23, filtering techniques are used. DCT is a technique with the ability to remove noise from signals as shown in [Saraiva et al., 2018], in addition, noise suppression with DCT is not enough in itself, so in this work a new method of identifying exonic regions using cross correlation with DCT together with an FFT-based bandpass filter to decrease signal noise and find exonic regions.